Spina bifida: The management of extremity deformities in myelomeningocele - (:unkn) unknown (Springer Milan, 2008)
The spectrum of congenital neural tube defects, referred to as myelomeningocele (spina bifida), produces a wide variety of disabilities, ranging from benign defects in the skin of the back to devastating paralysis and deformity of the lower extremities, urinary and fecal incontinence, hydrocephalus, spasticity, and mental retardation. The care of children with myelomeningocele usually requires a multidisciplinary approach. Early intervention by a team of trained caregivers can significantly improve the disabilities and permit many children to be integrated into normal social environments with high levels of independence. This chapter describes the overall management of myelomeningocele with special emphasis on the orthopedic management. © 2008 Springer-Verlag Italia.